CREVICE VOLUMES CONTRIBUTION TO THE THC EMISSION IN A MEDIUM SPEED GAS ENGINE - Tuomala, Markus (My University, 2015)
The research problem of this thesis was to investigate the importance of medium speed gas engine cylinder crevice volumes, and their contribution to hydrocarbon emission. The work was divided into four objectives. The first objective was to identify the main crevices in a few Wärtsilä models of medium speed gas engines. The second objective was to study the theoretical potential to reduce or modify the defined crevices by new design solutions of the cylinder components. The third objective was to plan the experimental set up configurations for a test program. Finally, the fourth objective was to determine the overall hydrocarbon emission response of the minimized crevice volumes in a medium speed lean burn gas engine. In the study the optimization response of an individual crevice volume compared to the response of the other crevice volumes were examined. The study also resulted with a joint magnitude of contribution for the other hydrocarbon emission mechanisms, excluding the crevice volume hydrocarbon emission mechanisms. A portion of the internal combustion engine fuel is exhausted as hydrocarbon emission. The main sources of a spark ignited internal combustion engine hydrocarbon emission are generally considered the (1) flame quenching at the combustion cylinder cold walls, (2) crevice volumes located in the cylinder, (3) fuel absorption by the lubricating oil during compression and the desorbing during the expansion and the (4) incomplete combustion due to the inadequate combustion conditions. Information about the hydrocarbon emission mechanisms and the contribution of the different mechanisms can be found in the literature. The information is mainly regarding the stoichiometric gasoline engines. However, the relative importance of the different hydrocarbon emissions mechanisms of the medium speed gas engines is not widely studied. Medium speed gas engine combustion conditions are different for example with combustion temperature, relative size of the crevice volumes, compression ratio and air fuel ratio. In respect to the different conditions possibly also the hydrocarbon emission mechanisms operate differently compared to the more researched type of engines.
Keywords: Gas engines; hydrocarbon; THC; emissions; crevice volume; fi=Sähkö- ja energiatekniikan suunta|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|